2016
DOI: 10.1177/0735633116681303
|View full text |Cite
|
Sign up to set email alerts
|

Learning Object Retrieval and Aggregation Based on Learning Styles

Abstract: The main goal of this article is to develop a Management System for Merging Learning Objects (msMLO), which offers an approach that retrieves learning objects (LOs) based on students' learning styles and term-based queries, which produces a new outcome with a better score. The msMLO faces the task of retrieving LOs via two steps: The first step ranks LOs using a unified learning style model and creates better LOs by merging the top-ranked LOs. The second step maps LOs onto a hierarchy of concepts to avoid dupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The authors showed that there are favorable results for the experimental group, when by presenting the merged LOs to the students, it was possible to make the students focus on the subject of study, and avoid the distractions underlying the location of other materials that may or may not be related to their learning preference or of the study subject. A more detailed study by the same authors showed that the fusion of LOs was responsible for improving learning performance that may be related to cognitive load [16].…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed that there are favorable results for the experimental group, when by presenting the merged LOs to the students, it was possible to make the students focus on the subject of study, and avoid the distractions underlying the location of other materials that may or may not be related to their learning preference or of the study subject. A more detailed study by the same authors showed that the fusion of LOs was responsible for improving learning performance that may be related to cognitive load [16].…”
Section: Introductionmentioning
confidence: 99%